Proposal of a telecare system for monitoring glucose anomalous behavior in type-2 diabetes patients - Nieto Chaupis, Huber (2017)
In this paper we present a case study emphasizing the proposal of a telecare system which might be implemented in the first attention level belonging to health centers of Periurban zones of Lima city. Concretely, the system relies entirely in an algorithm which is based on a mathematical scheme that models the behavior of the glucose in type 2 diabetes patients under episodes of binge eating disorder. The model assumes that the patient follows a pharmacological prescription of metformin. The testing of the model is through the usage of computational simulation based on the Monte Carlo method. Thus, the efficiency of telecare system running in the first attention level is estimated to be of order of 75% roughly. According to our results, 1 of 3 patients might surpass the events of binge eating disorder and delay diabetes progress in a consistent manner.